Appealing to Faculty Gatekeepers: Motivational Processes for Intentions to Adopt an Evidence-B ased Intervention. (1st June 2022) - McPartlan, Peter; Thoman, Dustin B; Poe, Jennifer; A Herrera, Felisha; Smith, Jessi L
Abstract: What motivates faculty teaching gateway courses to consider adopting an evidence-based classroom intervention? In this nationally representative study of biology faculty members in the United States (N = 422), we used expectancy–value–cost theory to understand three convergent motivational processes the faculty members' underlying intentions to adopt an exemplar evidence-based classroom intervention: the utility value intervention (UVI). Although the faculty members perceived the intervention as valuable, self-reported intentions to implement it were degraded by concerns about costs and lower expectancies for successful implementation. Structural equation modeling revealed that the faculty members reporting lower intentions to adopt it tended to be White and to identify as male and had many years of teaching or were from a more research-focused university. These personal, departmental, and institutional factors mapped onto value, expectancies, and cost perceptions uniquely, showing that each process was a necessary but insufficient way to inspire intentions to adopt the UVI. Our findings suggest multifaceted, context-responsive appeals to support faculty member motivation to scale up adoption of evidence-based classroom interventions.